(untitled) (Studia theodisca, 2019)
The aim of this article is to reconstruct the translation framework within which the rediscovery of Hölderlin in the George Circle takes place, with the intention of demonstrating why Hölderlin’s translation work plays a paradigmatic role for its members. Placed by the members of the Circle in immediate continuity with the Frühromantik and therefore considered as a forerunner of symbolism, Hölderlin represents a model of versification that combines movement and form. Hölderlin’s paradigmatic role among George’s disciples concerns above all his research on the poetic word. This aspect of his poetics could be principally perceived – in antithesis to Wilamowitz’s domesticating versions – in his deliberate introduction of “foreignizing” linguistic features into his translations from ancient Greek.